AB1051 Ultrasonography and power doppler ultrasonography of knee joint in patients with hepatitis c virus related arthritis. (15th June 2017) - Elgohary, R; Khalil, A; Ragab, G
Abstract : Background: HCV is a hepato-lymphotropic virus. Chronic arthritis is one of its extrahepatic manifestations 1 . The high frequency of rheumatoid factor (RF) positivity in HCV patients makes it difficult to differentiate between rheumatoid arthritis (RA) and HCV-related arthritis (HCVrA). An accurate and early diagnosis of HCVrA is important to avoid unnecessary immunosuppressive therapy 2 . Ultrasonography provides safe and quick access for the diagnosis of many rheumatic diseases. Objectives: To illustrate ultrasonographic findings obtained in knee joints of patients with HCVrA & to compare these findings with those obtained from knee joints of RA patients. Methods: Fifteen patients with HCVrA & 15 RA patients were subjected to: full history, clinical examination, Ultrasonography assessment using a Philips HDI 5000 system with 12–5 MHz Broadband Linear Transducer. Both knees were examined by one ultrasonographer who was blind to clinical data. Results: In HCVrA, synovial hypertrophy was detected in 10% of knees (3/30) of which 66% (2 knees) exhibited Doppler signals, while in RA it was detected in 70% (21/30) of which 95% (20 knees) exhibited Doppler signals. Significant difference was found between the two groups (p<0.01). Knee effusion was detected in 80% (24/30), & 86% (26/30), of patients with HCVrA & RA respectively, no significant difference was found. Cartilage degeneration was detected in 76% (23/30) & 83% (25/30), of patients with HCVrA & RA respectively. Bone erosions were detected in 20% (6/30) in the RA group. It was not detected in HCVrA patients. In HCVrA, there was no correlation between the presence of synovial hypertrophy with respect to cartilage degeneration and knee effusion. Conclusions: We found no specific ultrasonographic feature specific for HCV related knee arthritis, the knee effusion is a predominant feature and the hypertrophied synovium is not frequently found. No destructive lesions were found to be related to the disease itself; however this should be confirmed by histopathological assessment. References: Craxì Antonio, Laffi Giacomo & Zignego Anna Linda. Hepatitis C virus (HCV) infection: A systemic disease. Molecular Aspects of Medicine 2008;29:85. Rosner Itzhak, Rozenbaum Michael, Toubi Elias, Kessel Aharon, Naschitz Jochanan, and Zuckerman Eli. The Case for Hepatitis C Arthritis, Seminars in Arthritis and Rheumatism 2004;33:377–379, 381–382. Disclosure of Interest: None declared